Long-term equalization effects in Li-ion batteries due to local state of charge inhomogeneities and their impact on impedance measurements. (10th December 2015) - Kindermann, Frank M.; Noel, Andreas; Erhard, Simon V.; Jossen, Andreas
Abstract: Electrochemical impedance spectroscopy (EIS) is a powerful technique for characterizing Li-ion batteries. Besides the well-known state variables such as state of charge (SOC), state of health (SOH) and temperature, relaxation time after previous conditioning has a crucial impact on EIS measurements. By showing the EIS dependencies of three different temperatures, five SOCs and five cells with different cathode chemistries towards relaxation behavior, the importance of acknowledging relaxation time as an inner state is emphasized. After a single 1C cycle a deviation in the spectra compared to the relaxed state is detectable for up to 40 hours. In order to explain relaxation behavior, a mind model is introduced, which accounts for three equalization effects inside a particle and through an electrode layer. By means of a 1-D Newman model implemented in COMSOL Multiphysics 4.3b, two of the three proposed effects are discussed in more detail. Qualitatively, simulation data show the same dependencies towards relaxation as the experimental data, indicating that the model is a proper tool to investigate processes inside a cell. Certain deviations between experimental and modeling data can be explained by the 1-D approach and the fact that wiring and cell connections are not accounted for in the model. Modeling results strongly indicate that relaxation processes mainly take place in the graphite anode, which is assumed to be due to the flat open-circuit potential of graphite.